Entropy and renormalized solutions to the general nonlinear elliptic equations in Musielak–Orlicz spaces. (October 2021) - Li, Ying; Yao, Fengping; Zhou, Shulin
Abstract: In this paper we mainly prove the existence and uniqueness of entropy solutions and the uniqueness of renormalized solutions to the general nonlinear elliptic equations in Musielak-Orlicz spaces. Moreover, we also obtain the equivalence of entropy solutions and renormalized solutions in the present conditions.